2016
DOI: 10.3390/ma9100801
|View full text |Cite
|
Sign up to set email alerts
|

The Structural, Photocatalytic Property Characterization and Enhanced Photocatalytic Activities of Novel Photocatalysts Bi2GaSbO7 and Bi2InSbO7 during Visible Light Irradiation

Abstract: In order to develop original and efficient visible light response photocatalysts for degrading organic pollutants in wastewater, new photocatalysts Bi2GaSbO7 and Bi2InSbO7 were firstly synthesized by a solid-state reaction method and their chemical, physical and structural properties were characterized. Bi2GaSbO7 and Bi2InSbO7 were crystallized with a pyrochlore-type structure and the lattice parameter of Bi2GaSbO7 or Bi2InSbO7 was 10.356497 Å or 10.666031 Å. The band gap of Bi2GaSbO7 or Bi2InSbO7 was estimate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 80 publications
(82 reference statements)
0
5
0
Order By: Relevance
“…As shown in Figure 7 b,c, the calculational k value of BiSnSbO 6 for the phenol photodegradation was higher than that of N-doped TiO 2 . Above results demonstrated that the photosensitive effect was not a main factor in the photodegradation process of RhB with BiSnSbO 6 as a photocatalyst and BiSnSbO 6 itself had photocatalytic activity [ 54 , 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figure 7 b,c, the calculational k value of BiSnSbO 6 for the phenol photodegradation was higher than that of N-doped TiO 2 . Above results demonstrated that the photosensitive effect was not a main factor in the photodegradation process of RhB with BiSnSbO 6 as a photocatalyst and BiSnSbO 6 itself had photocatalytic activity [ 54 , 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…Zero-order kinetic models are typical of reactions where the surface of active sites is quickly saturated and mass diffusion, rather than the concentration of reactive species, becomes the controlling stage. , The fastest degradation rate was assigned to a 4.1 atom % N loading, presenting a kinetic constant of 1.9 × 10 –3 min –1 , whereas the rate became progressively slower upon the addition of further N doping. Compared to N-doped TiO 2 NPs, the kinetic constant was of the same order of N-doped TiO 2 fabricated by the sol–gel method . Furthermore, TiO 2 –N containing 4.1 atom % of N presented a slightly superior kinetic constant than N-doped sputtered TiO 2 films presenting N concentration of 1.2 atom % .…”
Section: Results and Discussionmentioning
confidence: 86%
“…Compared to N-doped TiO 2 NPs, the kinetic constant was of the same order of N-doped TiO 2 fabricated by the sol−gel method. 104 Furthermore, TiO 2 −N containing 4.1 atom % of N presented a slightly superior kinetic constant than N-doped sputtered TiO 2 films presenting N concentration of 1.2 atom %. 31 Interestingly, TiO 2 nanospheres containing TiO 1−x N x could lead to the fastest degradation of MB by nitriding TiO 2 nanosphere for at least 7 h at 700 °C.…”
Section: Resultsmentioning
confidence: 91%
“…The conventional processing methods that we used to degrade those dye contaminates were bio-degradation, electrochemistry, adsorption and flocculation-precipitation [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. However, because of the shortcomings and limitations of each method, the conventional methods of treating wastewater cannot achieve the maximum degradation effect [ 23 ]. Since 1972, photocatalytic reaction was firstly found, the photocatalysis technology had been booming due to the strong market demand [ 24 ], and is widely used in sewage treatment [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%